(3GdaQb aj GddZIs - (3KGHJ Hf CHj KGHJ SYjO Gdchaj , CHh eMeO,J (B250 (3g` s
(3ChdgG (B:s
(3bGd KGHJ Hf CHj KGHJ (B: (3gPG cJGH eG NGda ajg JSejI LhGQM GdEfSGf JSejI LhGQM PhGJ GdCQHY ef GdHgGFe hGdSHGY hZjQ Pdc s
(3BNQgG (B:s
(3GdJfGS (B: (3GdSjQ GdSQjY GdTOjO Ci dfG TjFkG ef GdShjb hZjQg GfQMd bHd Cf jOQcfG GdWdH Je GcJGH GdaQb hGdMeO ddg QH GdYGdejf s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B97 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B100 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B248s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JQeje s
Keywords: (3GddZIs